EVALUATION OF UTILIZATION ACTIVITIES OF DIGITAL MARKETING LANDING PAGES FOR SMALL BUSINESSES AT SALES VOLUME - Chandra, Eddy; Basuki Rachmat (Bajang Institute, 2025)
Thisistudy is a form ofievaluation of activitiesicarried out byesmall clothing business owners in RW 02 TlogomasMMalang with the aim ofeidentifying problems, causes and finding solutions. Aftereobtaining informationefrom sources oreinformants who were contacted that; in general,enamely 55% since June 2024 haveenot had an impact on increasing sales, then 25% saidethere was an increase inesales while 15% said sales were relatively stable andethere were 5% whoeexperienced a decrease inesales results. The main cause of theeproblem faced is the lackeof ability to utilize 'landingepages', namely 60%, and only 30% caneutilize the media and 10% onlyetry and doenot use 'landing pages' as a medium forepromotion. Theseeresults certainlyeneed to be followed up, namely by providing maximumetraining for the use of 'landingepages' for the small business owners in question.